OPTIMALIZATION OF SCIENCE LABORATORY TO IMPROVE THE INTEREST OF STUDY FOR STUDENTS IN SMP-IT IQRA’ MEDAN - Sinaga, Muhammad Zulham Efendi; Sihombing, Yuan Alfinsyah; Syahmarani, Aghni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Laboratories are very important in primary and secondary educational levels. Laboratories with practical activities can help students understand the concepts they have learned in class so as to increase their learning interest in science. One of the competencies in the learning process is the ability of students to solve problems in their life. This can be achieved with the help of laboratories and teaching aids available at the school. The psychomotor abilities of students will be honed in solving problems related to science concepts. Community service activities are carried out by several methods, the initial survey of partner problems, designing teaching aids and practicum equipment, simple practicum in the laboratory and making a practical guidebook. In the lab activities in the laboratory, the pre-test value was obtained with an average of 51.38 with the highest score was 70 and the lowest was 20. While the post-test score had an average of 79.31 with the highest score was 100 and the lowest was 30. The pre-test and post-test results showed an increase in the average value of students by 54.36%.